Métodos de agrupamento na análise de dados de expressão gênica - Rodrigues, Fabiene Silva (Universidade Federal de São Carlos, 2009)
The clustering techniques have frequently been used in literature to the analyse data in several fields of application. The main objective of this work is to study such techniques. There is a large number of clustering techniques in literature. In this work we concentrate on Self Organizing Map (SOM), k-means, k-medoids and Expectation- Maximization (EM) algorithms. These algorithms are applied to gene expression data. The analisys of gene expression, among other possibilities, identifies which genes are differently expressed in synthesis of proteins associated to normal and sick tissues. The purpose is to do a comparing of these metods, sticking out advantages and disadvantages of such. The metods were tested for simulation and after we apply them to a real data set.
Keywords: Análise multivariada; Método de agrupamento; Fator de Bayes; Modelos com misturas; Algoritmo EM; Expressão gênica; Seleção de modelos; Self Organizing Map (SOM); K-means; K-medoids; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA